Face Recognition Implementation as an Attendance Feature on Web-Based Video Conference Application - Robin; Fransiskus Hermanto; Wenripin Chandra (Brilliance: Research of Artificial Intelligence, 2023)
Online meeting by video conference has been used extensively in business, government, education and many more. One important aspect in doing online meeting is making sure the attendees recorded. In order to make attendance record, the hosts often have to spend some time to do attendance record because most of video conference applications do not have automatic attendance feature. To ease the meeting host in creating attendance record, we utilized computer vision to do attendee face recognition and then record the identity of the face owner and implement this into a web application to facilitate the usage in real life situation